النقوش النبطية وعلاقتها بقواعد النحو العربي: دراسة وصفية / The Nabatean Inscription and its relation with the Arabic grammar: A descriptive study - (Solehah Yaacob), صالحة يعقوب (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2015)
ملخص البحث: يهدف هذا البحث إلى إعادة قراءة تاريخ وضع النحو العربي وأصوله، والسؤال المطروح هو عما إذا كان العرب قد وصل العرب من دون تأثير خارجي إلى المفاهيم اللغوية الأساسية في تأسيس فكرهم اللغوي من تحليل لأجزاء الجمل والكلمات، واستنباط الاستخدام الصحيح من البيانات. وأما قول المستشرقين بأن اللغة العربية فلم تكن مكتملة إلا بعد بعثة رسول الله ﷺ فهو قول منقوضٌ لوجود البراهين عن وجوده قبل فجر الإسلام عبر اللهجات التي كانت مستخدمة منذ القديم في وادي الرافدين، وقد كان لهذه الأدلة إسهام في مجال النقد في الدراسة التارخية للغة العربية وقواعدها؛ إذ اكتشف البحث بعض الأدلة على عدم تأثرها بالثقافات الأخرى عبر القياس في آيات القرآن الكريم والنثر والشعر العربي وبعض الأمثلة من بعض كتب المترجمين، فضلاً عن بعض النماذج اللغة النبطية القديمة التي تشير إلى أن ما وضع من اللغة العربية وقواعدها كان فعلاً من ابتكار العرب وليس من غيرهم. الكلمات المفتاحية: الأصول- النقوش القديمة- اللغة العربية- القواعد- النحاة. Abstract: The study aims at reviewing the history of establishing the Arabic grammar and its foundations. It will examine whether the Arabs were similar to other nations in establishing their own grammatical rules by observing their language and the parts of its words and sentences without any external influences. As for the claim of some orientalists that Arabic only emerged after the Prophet Muhammad Pbuh, it is baseless as the language had already existed in the forms of dialects that were widespread in the area. These indications are critical to the study of the history of Arabic language and its grammar. Among the conclusions of the study are: the verses of the Quran, prose, grammar and some examples from the books of translators in addition to the samples of old Nabatean language give a strong indication that establishment of the Arabic grammar was the result of the efforts of the Arabs and without any foreign influences. Keywords: foundations– old inscriptions– Arabic language– grammar– grammarians. Abstrak: Kajian ini bertujuan untuk melihat semula sejarah kemunculan nahu bahasa Arab dan asas-asasnya. Ia akan melihat samada orang Arab adalah juga sebagaimana masyarakat-masyarakat lain dalam mewujudkan rumus tatabahasa mereka sendiri dengan mengkaji sifat Bahasa mereka dan bahagian perkataan serta ayatnya tanpa terdapat sebarang pengaruh luar. Bagi dakwaan beberapa orientalists tentang kemunculan Bahasa Arab itu secara lengkap hanya berlaku selepas Nabi Muhammad PbuH,ia adalah tertolak kerana Bahasa Arab telah pun wujud dalam bentuk dialek yang meluas dikawasan tersebut. Tanda-tanda ini kritikal kepada kajian sejarah Bahasa Arab dan tatabahasanya. Antara kesimpulan kajian ialah: puisi Quran, prosa, tatabahasa dan beberapa contoh dari buku penterjemah disamping sampel Bahasa Nabatean lama memberi satu petunjuk kukuh bahawa pengasasan nahu Bahasa Arab itu merupakan hasi lusaha orang Arab sendiri tanpa wujudnya pengaruh-pengaruh asing. Kata kunci: Asas-asas– Inskripsi kuno– bahasa Arab– tatabahasa– Ahli Bahasa.